(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
The use of additives plays a crucial role in providing energy sources for microorganisms during the ensiling process, enabling optimal physical quality of silage to be formed. Avocado seed meal (ASM) provides gradually released energy to support fermentative activity, while expired commercial syrup (ECS) contains easily degradable sugars that accelerate lactic acid production. The synergy between these two helps the preservation process occur more rapidly, allowing silage to reach stable conditions and exhibit better physical characteristics. This study was designed to evaluate the influence of these two materials in fattening sheep concentrate formulations, with a focus on changes in physical characteristics and acidity levels as benchmarks of fermentation success. The research was conducted using a Completely Randomized Design with five treatments and five replications, where ASM and ECS were administered at levels of 1.50%, 3%, 4.50%, and 6.00% of dry matter, while the base treatment without additives served as the control. The observed variables included silage aroma, texture, and color characteristics, as well as dry matter content, dry matter loss, pH value, and Fleigh Value as indicators of fermentation stability. The obtained data were analyzed using analysis of variance, followed by DMRT test at a 1% significance level. The research findings demonstrated that the combination of ASM and ECS had a highly significant effect (p<0.01) on the aroma, texture, color, pH, and Fleigh Value of fattening sheep concentrate silage, except that dry matter content and dry matter loss were not affected by the two additives. Treatment P5 (addition of ASM and ECS at 6% DM) emerged as the most superior treatment, characterized by strong fermentative aroma (3.32±0.06), smoother texture without clumping (3.49±0.07), more consistent yellowish-brown color (3.47±0.05), lower pH (4.31±0.07), and the highest Fleigh Value (98.9±1.05) as an indication of superior fermentation quality. In conclusion, the combination of avocado seed meal and expired commercial syrup at a dose of 6% of dry matter (3% ASM + 3% ECS) is recommended as an effective local additive to improve the physical quality and fermentation stability of fattening sheep concentrate silage.